Ecological effects of B. subtilis C3 in kiwifruit rhizosphere soil and its prevention and control against root rot disease - Guoyi, Xu; Xiaolong, Song; Yongli, Ku; Yuan, Tian; Ming, Li; Cuiling, Cao; Huili, Yu; Peng, Si (Frontiers in Microbiology, 2025)
As the world’s largest producer of kiwifruit, China faces significant yield and quality losses due to the widespread occurrence of kiwifruit root rot. To explore alternative biological control strategies for kiwifruit root rot, this study isolated 11 fungal isolates from diseased kiwifruit roots and identified Fusarium solani as the primary pathogen. Additionally, a biocontrol strain, Bacillus subtilis C3, was isolated from the rhizosphere of healthy kiwifruit and shown to significantly inhibit pathogen growth. The B. subtilis C3 strain effectively controls root rot via multiple mechanisms, including direct antagonism, secretion of antimicrobial proteins, promotion of seedling growth, and induction of plant defense enzymes. In pot and field trials, C3 treatment increased root fresh weight by 84.1%, enhanced root SOD and APX activities by 45.7 and 38.2%, respectively, and reduced disease severity. Moreover, C3 improved rhizosphere soil microbial diversity of the Rhizosphere, with the Shannon index increasing from 3.0 to 3.4. Unlike previous studies focusing solely on pathogen suppression, this work highlights the dual role of B. subtilis C3 in controlling root rot and restoring rhizosphere ecological function, offering a green and sustainable biocontrol strategy for kiwifruit production.